Lenses on teaching : developing perspectives on classroom life - Chiarelott, Leigh; Ryan, Kevin; Davidman, Leonard (Fort Worth, TX : Harcourt Brace College, 1998)
Introduction to lenses on teaching. Orienting yourself to schools. School restructuring and teachers' professional development. Observing classroom interaction. Developing interviewing skills...
Keywords: Education; Teaching; Teachers; Observation; Observation (Educational method); Teaching; Teachers -- Training of